Kajian Urgensi Kemitraan Publik Swasta di Kota Palembang - Fitriani, Helda (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
The desire of the Palembang City government to work on colorful systems with Public Private hookups (PPP) medium, driven by limited backing sources, mortal coffers, technological capabilities and so forth. This case do for realizing the" Palembang Champion Program". The desire of the Palembang mega city government is grounded on this thinking that the Government is obliged to fulfill sociolect- profitable liabilities to the community, and to insure public services can be carried out with good for all of society. The purpose of this jotting is to dissect the Public Private hookups (PPP) cooperation scheme applicable for the government of Palembang mega city. The system used in this paper is a descriptive study with literature ways, is looking for theoretical references that are applicable to the cases or problems set up, is the problem of public private cooperation cooperation between the Palembang mega city government and the private sector in the provision of public services. The type of data is secondary data attained from media and internet attestation as well as sources from books and library sources others that support the discussion in this study. So that the collaboration between the public private cooperation of the Palembang mega city government and the private sector is successful several effects that must be considered, videlicet this cooperation must be strategically important for both parties, are reciprocal rather than mutually competent, openness will information on both sides and should engender genuine integration links despite artistic differences. collective trust is the main thing. The form of public private cooperation cooperation with the mega city government Palembang with private parties can be in the form of a Service Contract, Lease Contract or or figure- Operate- Transfer/BOT Contract or figure Manage and Transfer Property Public-Private Partnership doesn’t always have a bad connotation, to be successful there are numerous terms and conditions Must be fulfilled. It’s intended that the government gets the stylish results, the people too gain a commensurable result, videlicet weal. therefore the spirit of Public- Private Partnership is to strengthen the government or ameliorate public services that have been assessed so far not yet effective